Building a Robot Tractor Using Commercial Components and Widely Used Standards. Issue 32 (2022) - Backman, Juha; Linkolehto, Raimo; Lemsalu, Madis; Kaivosoja, Jere
Abstract: The development of the robot tractors has been ongoing for a long time already. There are even commercial applications available. However, still the robot tractor is rare in use in farms. In other developments in agricultural technology, it has already been recognized that the standard is the key to the widespread adoption of technology. The ISO 11783 standard is widely accepted communication standard for agricultural machinery. The standard defines many devices that can be used in precision farming. By using the standard, the devices and the implements of different manufacturers are compatible with each other. The state-of-the-art tractor already includes many functionalities that the robot tractor needs. The objective of this research was to build a robot tractor using existing commercial components and to find suitable standards that are already adopted in the agriculture. The robot functionality will be an accessory that operates with existing components. By that way, we try to answer the research question how the robots could become more widely used.